Contribution of Socioeconomic Status to Racial/Ethnic Disparities in Adverse Pregnancy Outcomes Among Women With Systemic Lupus Erythematosus. Issue 2 (29th December 2017) - Kaplowitz, Elianna T.; Ferguson, Sancia; Guerra, Marta; Laskin, Carl A.; Buyon, Jill P.; Petri, Michelle; Lockshin, Michael D.; Sammaritano, Lisa R.; Branch, D. Ware; Merrill, Joan T.; Katz, Patricia; Salmon, Jane E.
Abstract : Objective: We examined rates of adverse pregnancy outcomes (APO) by race/ethnicity among women with systemic lupus erythematosus (SLE), with and without antiphospholipid antibodies (aPL), and whether socioeconomic status (SES) accounted for differences. Methods: Data were from the PROMISSE (Predictors of Pregnancy Outcome: Biomarkers in Antiphospholipid Antibody Syndrome and Systemic Lupus Erythematosus) study, a multicenter study that enrolled 346 patients with SLE and 62 patients with SLE and aPL (50% white, 20% African American, 17% Hispanic, 12% Asian/Pacific Islander). Measures of SES were educational attainment, median community income, and community education. Logistic regression analyses were conducted to determine odds of APO for each racial/ethnic group, controlling first for age and clinical variables, and then for SES. Results: The frequency of APO in white women with SLE, with and without aPL, was 29% and 11%, respectively. For African American and Hispanic women it was approximately 2‐fold greater. In African American women with SLE alone, adjustment for clinical variables attenuated the odds ratio (OR) from 2.7 (95% confidence interval [95% CI] 1.3–5.5) to 2.3 (95% CI 1.1–5.1), and after additional adjustment for SES, there were no longer significant differences in APO compared to whites. In contrast, in SLE patients with aPL, whites, African Americans, and Hispanics had markedly higher risks of APO compared to white SLE patients without aPL (OR 3.5 [95% CI 1.4–7.7], OR 12.4 [95% CI 1.9–79.8], and OR 10.4 [95% CI 2.5–42.4], respectively), which were not accounted for by clinical or SES covariates. Conclusion: This finding suggests that for African American women with SLE without aPL, SES factors are key contributors to disparities in APO, despite monthly care from experts, whereas other factors contribute to disparities in SLE with aPL.